EGFR and EGFRvIII analysis in glioblastoma as therapeutic biomarkers. (2nd January 2015) - Faulkner, Claire; Palmer, Abigail; Williams, Hannah; Wragg, Christopher; Haynes, Harry R.; White, Paul; DeSouza, Ruth-Mary; Williams, Maggie; Hopkins, Kirsten; Kurian, Kathreena M.
Abstract: Introduction. EGFR and EGFRvIII analysis is of current interest because of new EGFRvIII vaccine trials opened in the UK. EGFR activation promotes cellular proliferation via activation of MAPK and PI3K-Akt pathways. EGFRvIII is the most common variant resulting from an in-frame deletion of 801bp, leading to constitutively active EGFR. Method. 51 glioblastoma samples from a cohort of 50 patients were tested for EGFR amplification by FISH and immunohistochemistry and EGFRvIII expression by reverse-transcriptase PCR (RT-PCR), and immunohistochemistry. EGFR and EGFRvIII expression was compared with Overall Survival in the cohort. Results . Overall 22/51 samples (43%) were positive for EGFR, 16/51 (31%) were positive for EGFRvIII and 13/51 (25%) were positive for both. 9/51 cases (18%) were positive for EGFR alone, and 3/51 (6%) were positive for EGFRvIII alone. Of the EGFR positive cases, 22/51 (43%) were positive by FISH, 24/51 (47%) were positive by IHC and 2/51 (4%) were discrepant between methods (positive by IHC but non-amplified by FISH). Of the EGFRvIII positive cases, 16/51 (31%) were positive by RT-PCR, 17/51 (33%) were positive by IHC and 1/51 (2%) sample was discrepant (positive by IHC but not by RT-PCR). Neither EGFRvIII or EGFR are predictive of overall survival in this cohort. Conclusion. In our cohort, 25/51 (49%) of GBM showed EGFR alterations, including 16/51 (31%) with EGFRvIII. There was high concordance between IHC and FISH (96%) and IHC and RT-PCR (98%) as diagnostic methods. Neither EGFR or EGFRvIII is predictive of overall survival in this cohort. These results are key for selecting patients for novel individualised anti-EGFR therapies.